A procedure for sensory detection of androstenone in meat and meat products from entire male pigs: Development of a panel training. (December 2016) - Garrido, Mª. Dolores; Egea, Macarena; Linares, Mª. Belén; Martínez, Beatriz; Viera, Ceferina; Rubio, Begoña; Borrisser-Pairó, Francesc
Abstract: This study represents a proposal for training sensory panels in androstenone (AND) perception in meat and meat products. The procedure consists of four main parts: (1) selection and training of a sensory panel (11 panelists) using standards with Vaseline oil media as carriers of AND and skatole (SKA); (2) developing a training method AND detection in meat; (3) dry cured meat product and (4) cooked meat product. All candidates were able to distinguish between AND, SKA and AND + SKA in Vaseline oil, order AND solutions with different concentrations and classify them in the three categories: low, medium and high. The panel was able to differentiate the meat in the three categories, but only the high level in meat products. Due to the individual features in AND perception, specific training for each type of product is required. Highlights: All panelist were selected and trained using standards of androstenone and skatole in vaseline oil. Not all the panelists were able to detect AND in meat and meat products. The selected sensory panel was able to differentiate high levels of androstenone in meat products. Composition, processing and consumption conditions and individual threshold may modify AND perception.